ANALISIS FAKTOR PENYEBAB DAN PENANGGULANGAN KERUSAKAN RUAS JALAN BURIA-RIRING KABUPATEN SERAM BAGIAN BARAT - Richard Makaruku; Elisabeth Talakua; Godfried Lewakabessy (Jurusan Teknik Sipil, 2023)
The Buria-Riring Road section is located in Taniwel District, West Seram Regency, Maluku Province. This road section was built in 2019. However, in the middle of 2021 this road experienced damage. The topographic condition of the road section is in the mountains with many hills and slopes, plus the high level of rainfall means that rainwater that falls directly floods the road body and damages the pavement structure. With this condition, people no longer feel comfortable accessing this road. The purpose of this study is to determine the type of damage that occurs and what factors cause the damage, as well as find solutions to overcome the damage that occurs in the form of planning pavement thickness and planning drainage channel dimensions. The method used for planning the thickness of the flexible pavement is the 2017 Pavement Design Manual and calculating the dimensions of the drainage channels. From the results of the analysis, the type of damage that occurs is the release of grains (Raveling) and the causative factors are not built drainage channels and the carrying capacity of subgrade soils that are less stable. From the calculation results, it is obtained that the thickness of the stabilized subgrade is 175 mm, the aggregate base layer for class B is 100 mm, the base layer for class A aggregate is 200 mm, the burda with an aggregate size of at least 20 mm. And from the results of the calculation of the dimensions of the drainage channel, it is obtained that the width of the base of the channel is 55 cm, the width of the top of the channel is 90 cm and the depth of the channel is 75 cm.